Advanced physics series. Einstein's heroes : Newton, Faraday, and Maxwell / [presented by Dr. Robyn Arianrhod] - Arianrhod, Robyn (Rees Films, 2009)
Dr. Robyn Arianrhod, a writer and mathematician at Monash University, traces the connections between the development of electrodynamics by Faraday and Maxwell, and Einstein's Theory of Special Relativity. Along the way, she looks at the roles both mathematics and experimentation have played in establishing these key areas of modern physics.